Calculation of optimal jaw geometry for an electronic bond pull test. (August 2014) - Symons, Digby D; Chen, Jialiang; Alton, Padraig
A bond pull test is used to determine the strength of the bond of an electronic interconnect to a circuit board. A standard test consists of clamping and pulling the interconnect with a pair of microscopic jaws. In a successful test, the maximum pulling force registered by the jaws will be the failure load of the interconnect to circuit board bond. However, if the interconnect itself deforms before the bond has failed, then this would constitute an unsuccessful test. This paper reports on a theoretical analysis of the optimal geometry for gripping of a cylindrical interconnect. Upper and lower-bound plasticity models have been used to determine the jaw proportions that will maximize the load for the deformation of the interconnect and that should, therefore, be most likely to allow successful measurement of the bond strength. This theoretical analysis is compared to 2D and 3D non-linear finite element calculations. The 2D finite element models are axi-symmetric approximations of a pull test on a cylindrical interconnect. 3D finite element models take into account the actual jaw geometry and allow simulation of both clamping and pulling stages. The maximum calculated pull forces for both 2D and 3D simulations are in good agreement with the plasticity theory. Preliminary validation of the theory and finite element results has been accomplished through experimental clamping and pulling tests on cylindrical metal rods.